Abnormal Activities of Tropical Cyclones in 2019 Over the Korean Peninsula. Issue 7 (1st April 2021) - Moon, M.; Ha, K.‐J.
Abstract: Approximately, 25.6 tropical cyclones (TCs) occur in the western North Pacific (WNP) each year, of which 3.4 TCs affect the Korean Peninsula (KP). In 2019, a record of seven TCs affected the KP. We investigated and elucidated the favorable conditions influencing the TCs approaching the KP using the Weather Research and Forecasting model version 4.0 (WRFv4). The cold Maritime Continent‐warm WNP sea surface temperature (SST) was found to be a major factor. The effect of the SST gradient was examined for one representative case using WRFv4 with varying SST anomalies. This study suggests that the SST gradient‐induced change in the circulation over the Maritime Continent is a main factor causing the TCs to approach the KP. Plain Language Summary: In 2019, typhoons over the western North Pacific occurred as expected, but the number of typhoons affecting the Korean Peninsula (KP) was the highest in the last 60 years. We used the tropical cyclone (TC) information provided by the Regional Specialized Meteorological Center, Tokyo from 1958 to 2019 to understand the TC activity affecting the KP by analyzing the reanalysis data and numerical model experiments. We examined the characteristics of surrounding atmospheric spatial patterns relating to TC activities affecting the KP. The results show that the changes in the sea surface temperature gradients drive the surrounding weather patterns, creating favorable conditions for TCs affecting the KP. Key Points: This study aims to investigate the favorable conditions for tropical cyclones that affect the Korean Peninsula Cold sea surface temperature anomalies over the Maritime Continent created favorable conditions for tropical cyclones affecting the Korean Peninsula Numerical experiments support that the sea surface temperature gradient has an influence on tropical cyclone activity